The potential of the Microsoft Kinect in sports analysis and biomechanics - Choppin, S.; Wheat, J. (Sports Technology, 2013)
The objective of this study was to assess the suitability of the Microsoft Kinect depth camera as a tool in segment scanning, segment tracking and player tracking. A mannequin was scanned with the Kinect and a laser scanner. The geometries were truncated to create torso 'segments' and compared. Separate shoulder abduction (-100° to 50°) and flexion motions (0°-100°) were recorded by the Kinect (using free and commercial software) and a Motion Analysis Corporation (MAC) system. Segment angles were compared. A participant's centre of mass (COM) was tracked over a 6 x 3 m floor area using the Kinect and a MAC system and compared. Mean errors with uncertainty of the mass, COM position and principal moments of inertia were -1.9 ± 1.6%, 0.5 ± 0.4% and 3 ± 2.6%, respectively. The commercial software gave the highest accuracy, in which the maximum and root mean square errors (RMSEs) were 13.85° and 7.59° in abduction and 21.57° and 12.00° in flexion. RMSEs in X, Y and Z COM positions were 0.12, 0.14 and 0.08 m, respectively, although vertical position (Y) was subject to a large systematic bias of 405 mm. The Kinect's low cost and depth camera are an advantage for sports biomechanics and motion analysis. Although segment tracking accuracy is low, the Kinect could potentially be used in coaching and education for all three application areas in this study.